Politik Legislasi Dewan Perwakilan Daerah Republik Indonesia Pasca Putusan Mahkamah Konstitusi Nomor 92/PUU-X/2012 - King Faisal Sulaiman (Perspektif Hukum, 2015)
The Constitutional Court Decision, Number 92/PUU-X/2012 has opened a new legislation policy for the Senate of Indonesia. The impact of this decision can strengthen legislation competence to the Senate in inisiating the legal drafting, as attributed on Article 22D of the 1945 Constitution of Republic of Indonensia. The decision can be a landmark decision for struggling the strong bicameral system and presidential system after amendment of the 1945 Constitution. As the impact of the decision, the house of representatives must soon take legislative review especially to Act Number 27 of 2009 and Act Number 12 of 2011 to accommodate the legal substance of the decision (The Constitutional Court Decision, Number 92/PUU-X/2012).